2022
DOI: 10.3390/met12091508
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nb Addition on α″ and ω Phase Stability and on Mechanical Properties in the Ti-12Mo-xNb Stoichiometric System

Abstract: Metastable β-Ti alloys have become one of the most attractive implant materials due to their high biocorrosion resistance, biocompatibility, and mechanical properties, including lower Young’s modulus values. Mechanical properties of these alloys are strongly dependent on the final microstructure, which is controlled by thermomechanical treatment processing, in particular the Young’s modulus and hardness. The aim of this work was to analyze the influence of phase precipitations in heat-treated Ti–12Mo–xNb (x = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Each material emits a characteristic sound when struck that depends on its elastic properties, geometric dimension, and mass. The emitted sound contains information that allows the determination of elastic properties, such as the elastic modulus and the natural vibration frequencies [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each material emits a characteristic sound when struck that depends on its elastic properties, geometric dimension, and mass. The emitted sound contains information that allows the determination of elastic properties, such as the elastic modulus and the natural vibration frequencies [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Borborema et al [ 13 ] analyzed the influence of Nb content on the phases formed in the Ti-12Mo-Nb alloy (Nb = 0, 3, 8, 13, 17, and 20 wt%). The authors show that Nb acts as a stabilizing β element, suppressing the formation of the α” phase present in the Ti-12Mo alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Mo, in addition to being a β stabilizer, strongly contributes to increased strength and a reduced Young's modulus [24,25]. Niobium is also a β-stabilizing element [26]. Titanium alloys with Nb contents up to 15 wt % present a hexagonal α martensite phase after water quenching.…”
Section: Introductionmentioning
confidence: 99%